Combating Corruption in Croatia: From Expert Perceptions to Policy-Oriented Action Strategies and Back - Čaldarović, Ognjen (Array, 2009)
In this paper a comparative analysis of various perceptions of corruption in Croatia is presented. The investigation is based on the research results obtained within the FP6 project “ Crime as Culture” , started in 2006, which focused on the perception of corruption in seven European countries. The grounded theory method was used to organize and interpret data collected in interviews with experts from six target groups. The aim of this paper is to provide some policy- oriented insights based on a synthesis of the project findings. The paper is divided into four sections focusing on the major dimensions of combat against corruption: (1) research on corruption, (2) sanctioning corruption, (3) corruption prevention, and (4) increasing anti-corruption awareness. As our analyses suggest, the social embeddedness of corruption in Croatia is well reflected in the dominant expert perceptions of corruption. The observed heterogeneity and fragmentariness of the existing (and often competing) perceptions of corruption found in this study are potential obstacles to a systematic, well-coordinated, and efficacious anti-corruption strategy.